Mycolic Acid-Containing Bacteria Induce Natural-Product Biosynthesis in Streptomyces Species - Onaka, Hiroyasu; Mori, Yukiko; Igarashi, Yasuhiro; Furumai, Tamotsu (Applied and Environmental Microbiology, 2011)
Natural products produced by microorganisms are important starting compounds for drug discovery. Secondary metabolites, including antibiotics, have been isolated from different Streptomyces species. The production of these metabolites depends on the culture conditions. Therefore, the development of a new culture method can facilitate the discovery of new natural products. Here, we show that mycolic acid-containing bacteria can influence the biosynthesis of cryptic natural products in Streptomyces species. The production of red pigment by Streptomyces lividans TK23 was induced by coculture with Tsukamurella pulmonis TP-B0596, which is a mycolic acid-containing bacterium. Only living cells induced this pigment production, which was not mediated by any substances. T. pulmonis could induce natural-product synthesis in other Streptomyces strains too: it altered natural-product biosynthesis in 88.4% of the Streptomyces strains isolated from soil. The other mycolic acid-containing bacteria, Rhodococcus erythropolis and Corynebacterium glutamicum, altered biosynthesis in 87.5 and 90.2% of the Streptomyces strains, respectively. The coculture broth of T. pulmonis and Streptomyces endus S-522 contained a novel antibiotic, which we named alchivemycin A. We concluded that the mycolic acid localized in the outer cell layer of the inducer bacterium influences secondary metabolism in Streptomyces, and this activity is a result of the direct interaction between the mycolic acid-containing bacteria and STREPTOMYCES: We used these results to develop a new coculture method, called the combined-culture method, which facilitates the screening of natural products.